Research on the economic of clean energy heating systems in cold rural regions - MA Tianfeng; ZHANG Yaru; SHANG Tianwen (Dianxin kexue)
At present, the conventional heating methods in rural areas of northern China present challenges to carbon emission reduction efforts.Consequently, selecting appropriate clean energy heating methods in rural areas has emerged as a significant concern. The TRNSYS was used to simulation software to construct three decentralized clean energy heating systems-natural gas boiler heating, air source heat pump heating, and solar-coupled air source heat pump heating. Then, a typical rural household in Shanxi Province was taken as an example, simulations were conducted for the three systems. The research findings indicate that the solar-coupled air source heat pump heating system performs excellently in heating stability and operational efficiency. It exhibits the lowest operating costs over its lifespan, Moreover, the solar-coupled air source heat pump heating system is more conducive to carbon emissions reduction. These research results provide an important reference for choosing clean energy heating methods in rural areas of northern China, which can help guide policymaking and resource allocation and promote the popularization and application of clean energy heating in rural areas.